1996
DOI: 10.1097/00000658-199604000-00012
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Tumor Necrosis Factor- α in the Increased Mortality Associated with Vibrio Vulnificus Infection in the Presence of Hepatic Dysfunction

Abstract: Cirrhotic mice show increased mortality to Vibrio infection, and this increased mortality is dependent on an in vivo tumor necrosis factor-alpha response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 14 publications
2
30
0
Order By: Relevance
“…Additionally, CPS production is believed to constitute a primary virulence factor of V. vulnificus, which is essential for pathogenicity (5,22). The production of proinflammatory cytokines such as IL-1ß, TNF-·, and IL-6 has been reported in V. vulnificus-infected hosts (12)(13)(14)40). Our data demonstrated that TLR2 is the key receptor for V. vulnificus CPS-related immune response.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Additionally, CPS production is believed to constitute a primary virulence factor of V. vulnificus, which is essential for pathogenicity (5,22). The production of proinflammatory cytokines such as IL-1ß, TNF-·, and IL-6 has been reported in V. vulnificus-infected hosts (12)(13)(14)40). Our data demonstrated that TLR2 is the key receptor for V. vulnificus CPS-related immune response.…”
Section: Discussionsupporting
confidence: 53%
“…The majority of fatal cases are attributable to septic shock which results from a variety of virulence factors of V. vulnificus including lipopolysaccharide (LPS) (3), capsular polysaccharide (CPS) (4-6), siderophores (7), cytolysin (8), elastolytic protease (9), phospholipase A 2 (10), RTX toxin (rtxA) (11) and flagella (12). These virulence factors may persistently activate the generation of proinflammatory mediators such as tumor necrosis factor-· from the affected host (4,13,14). In particular, surface polysaccharides, including CPS and LPS, perform pivotal roles in the pathogenicity of gram-negative bacteria by assisting the bacteria in the evasion of host defenses (4,15).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, while much is now known about some of the bacterial factors involved in the disease process, little is understood about host cellular factors leading to susceptibility. It has been previously shown that V. vulnificus has the ability to elicit inflammationassociated cytokines from primary human cells in vitro and from animals in vivo (10,33). A recent study from Korea is the first to report significant increases in the levels of pro-inflammatory cytokines tumor necrosis factor alpha (TNF-␣), interleukin-1␤ (IL-1␤), and IL-6 in serum from V. vulnificus-infected patients compared to healthy individuals, confirming a role for dysregulation of the cytokine response (39).…”
mentioning
confidence: 99%
“…These host-or bacteria-derived factors may persistently activate the generation of proinflammatory mediators such as tumor necrosis factor-α, IL-1β, IL-6, IL-8, and nitric oxide from affected hosts (10,11). The majority of these mediators display multiple biological effects, and have been identified as key mediators in the pathophysiological alterations associated with septic shock.…”
Section: Introductionmentioning
confidence: 99%